A review of CFD modelling studies on the flotation process - Wang, Guichao; Ge, Linhan; Mitra, Subhasish; Evans, Geoffrey M.; Joshi, J.B.; Chen, Songying (Minerals engineering, 2018)
•CFD modelling studies on the flotation process are reviewed.•Advances in the flotation equipment modelling are analysed.•CFD methods for determining the effect of hydrodynamics are summarized.•Recommendations for future progresses are made. A comprehensive review of the published literature regarding the computational fluid dynamics (CFD) modelling of the flotation process is presented. The detailed principles, mechanism and operation of the flotation process are discussed focusing mainly on the hydrodynamic aspect which is required for the successful operation of the flotation cell. The kinetic modelling of flotation process has been reviewed in detail in three major flotation equipment namely mechanically agitated flotation cell, flotation column and dissolved air flotation. The advances made in the modelling and simulations of the equipment have been critically analyzed. Specific emphasis is given on the bubble-particle interactions and the effect of turbulence on these interactions. An attempt has been made to correlate the model parameters with the turbulence parameters. A thorough discussion is presented to highlight strengths and weaknesses of currently used CFD models and the recent developments in the numerical simulation tools for better understanding of the process. Finally, recommendations have been made for the future progress based on the analysis of the previous work.